Master Plan Initiative of Electronic-Based Government System (SPBE) in Metro City, Indonesia - Erizal Erizal; M Fairuzabadi; Zaidir Zaidir; A Roswiani (Universitas Respati Yogyakarta, 2022)
The central government expects the development of information technology and bureaucratic reform in the regions to be more focused and integrated. The problem that exists in the Metro City government is that there are still many government service information systems that have not been integrated or are still partial. The Metro City government's Electronic-Based Government System Index (SPBE) in 2021 is 2.17 with the predicate